Minutes of the EURISCO Advisory Group: Fourth meeting, 12 March 2008, Bonn, Germany [ECPGR Documentation and Information Network] - Maggioni, L.; Dias, S.; Bioversity International (2008)
Minutes of the fourth meeting of the EURISCO Advisory Group, 12 March 2008, Bonn, Germany